'To move or not to move': a national survey among professionals on beliefs and considerations about the place of end‐of‐life care for people with intellectual disabilities. (27th May 2014) - Bekkema, N.; de Veer, A. J. E.; Wagemans, A. M. A; Hertogh, C. M. P. M.; Francke, A. L.
Abstract Background The aim of this article was to investigate the beliefs and considerations of professionals concerning an appropriate environment for end‐of‐life care for people with intellectual disabilities (ID). Method A survey questionnaire was composed based on a scan of relevant literature and the results of group interviews with professionals, family members and people with ID. The questionnaire focused on the respondents' general beliefs about an appropriate environment for end‐of‐life care and their specific considerations regarding the place of care of the last client for whom the respondent provided end‐of‐life care. The questionnaire was sent to 294 care staff members recruited from a nationally representative panel of nurses and social workers, 273 ID physicians recruited from the members list of the Dutch professional association of ID physicians, and 1000 general practitioners (GPs) recruited from a nationally representative sample from a national registration of GPs. Results The overall response was 46%. Professionals predominantly believe that all efforts should be made to ensure that a person with ID receives end‐of‐life care in their own home environment, and that 24/7 care is available. Respondents indicated that most of the clients (79%) who had last received end‐of‐life care from an ID care service were able to stay in their own home environment. Decisions to keep the client in their own home environment were primarily based on the familiarity of the environment and the expertise of the team in end‐of‐life care. Insufficient expertise and a lack of adequate equipment were the main considerations in decisions to move a client. Despite the belief of care staff in particular that the wishes of the person with ID should always be leading when deciding on the place of end‐of‐life care, only 8% of the care staff and ID physicians explicitly mentioned that the client's wishes were taken into account in actual decision‐making. Conclusions Professionals agree that end‐of‐life care for people with ID should preferably take place in the client's home environment, even when nursing expertise, experience and adequate equipment are not (yet) in place. Nonetheless, a lack of expertise in end‐of‐life care is the foremost consideration in decisions to move a client. If ID care services want to promote end‐of‐life care in the client's own home, we recommend formulating a policy on how to realise end‐of‐life care in the client's own home environment and provide sufficient training and support for staff. To involve people with ID as much as possible, we recommend that professionals integrate more collaborative principles in decision‐making about the place of end‐of‐life care.